Alpha lipoic acid and green tea extract with oral antidiabetic therapy ameliorate hepatic damage in streptozotocin induced diabetic rats - NEVIEN M. AHMED,; HANAN A. SABRA, (International Journal of Pharma and Bio Sciences, 2018)
Diabetes Mellitus remains a fatal disorder worldwide. The major hallmark of diabetes is progression of the complications that includes liver damage. As a result of the limitations associated with the use of anti-diabetic drugs, an increased number of diabetic populations globally now choice to complementary and alternative medicine such as natural products. Rats with streptozotocin induced diabetes were subjected to antidiabetic drug metformin, Dietary green tea extract (GTE) and alpha lipoic acid (ALA) supplementations to evaluate their effects on oxidative and inflammatory liver parameters of experimental animals. Sixty male albino rats (150-200g) were divided randomly into 6 groups. Normal untreated group, Diabetic group where Diabetes was induced by a single intraperitoneal injection of streptozotocin (45 mg/kg). The treated groups received metformin Metformin (100 mg/ kg) + ALA (100 mg/kg, Metformin (100 mg/ kg) + GTE (45 mg/kg ), for 8 weeks. Finally, blood samples were collected and analyzed for glucose, insulin levels, lipid profile, oxidative stress parameters, inflammatory markers and histology findings. Administration of green tea extract and alpha lipoic acid with metformin caused a significant decrease in glucose, insulin, cholesterol, triglyceride levels and inflammatory markers and significantly improved the antioxidant parameters. Supplementation of nature antioxidant as green tea or alpha lipoic acid protects against STZ-induced hyperglycemia and oxidative stress in experimental rats. This study suggests that green tea extractor alpha lipoic acid ingested with anti-diabetic drugs as metformin may prove to be a useful therapeutic option in the reversal of diabetic dysfunction.